Ex Vivo Regional Gene Therapy Compared to Recombinant BMP-2 for the Treatment of Critical-Size Bone Defects: An In Vivo Single-Cell RNA-Sequencing Study - Arijita Sarkar; Matthew C. Gallo; Jennifer A. Bell; Cory K. Mayfield; Jacob R. Ball; Mina Ayad; Elizabeth Lechtholz-Zey; Stephanie W. Chang; Osamu Sugiyama; Denis Evseenko; Jay R. Lieberman (Bioengineering)
Ex vivo regional gene therapy is a promising tissue-engineering strategy for bone regeneration: osteogenic mesenchymal stem cells (MSCs) can be genetically modified to express an osteoinductive stimulus (e.g., bone morphogenetic protein-2), seeded onto an osteoconductive scaffold, and then implanted into a bone defect to exert a therapeutic effect. Compared to recombinant human BMP-2 (rhBMP-2), which is approved for clinical use, regional gene therapy may have unique benefits related to the addition of MSCs and the sustained release of BMP-2. However, the cellular and transcriptional mechanisms regulating the response to these two strategies for BMP-2 mediated bone regeneration are largely unknown. Here, for the first time, we performed single-cell RNA sequencing (10x Genomics) of hematoma tissue in six rats with critical-sized femoral defects that were treated with either regional gene therapy or rhBMP-2. Our unbiased bioinformatic analysis of 2393 filtered cells in each group revealed treatment-specific differences in their cellular composition, transcriptional profiles, and cellular communication patterns. Gene therapy treatment induced a more robust chondrogenic response, as well as a decrease in the proportion of fibroblasts and the expression of profibrotic pathways. Additionally, gene therapy was associated with an anti-inflammatory microenvironment; macrophages expressing canonical anti-inflammatory markers were more common in the gene therapy group. In contrast, pro-inflammatory markers were more highly expressed in the rhBMP-2 group. Collectively, the results of our study may offer insights into the unique pathways through which ex vivo regional gene therapy can augment bone regeneration compared to rhBMP-2. Furthermore, an improved understanding of the cellular pathways involved in segmental bone defect healing may allow for the further optimization of regional gene therapy or other bone repair strategies.